PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA MECHANICAL DIVISION PT MULIA MAKMUR ELEKTRIKATAMA - Nidaul Izzah; Ida Ardiani (Institut Ilmu Sosial dan Manajemen STIAMI, 2016)
The purpose of this study was to obtain information about the influence of compensation and working discipline on employee productivity, while the purpose is to obtain data empirically the extent of the influence of compensation and working discipline in increasing productivity employee. The data analysis method used is quantitative method. Quantitative methods are used to determine the relationship between the variable compensation (X1) and variable work discipline (X2) on employee productivity (Y).Samples were employees at mechanical division of PT Mulia Makmur Jalan Jababeka VIIIA Elektrikatama SFB Block B 11 V Cikarang Bekasi, sampling is done by random sampling. After examining the completed questionnaires that have been distributed to the employees and the calculation of the correlation between compensation and discipline against the labor productivity by using multiple regression calculations obtained: Y = 0.0102 + 0,2149X1 + 0,7998X2 with b1 = 0.2149 have meaning relationships compensation (X1) and productivity (Y) is positive and b2 = 0.7998 has meaning relations work discipline (X2) and productivity (Y) is positive. While the analysis results obtained using the calculation of multiple correlation R = 0.9113 and KPB = 83.05%, which means there is a very strong positive relationship between compensation and (X1) and discipline (X2) together to work productivity (Y) and 16.95% contribution comes from factors outside of this study. The F-test results showed Fhitung> Ftabel or 66.13%> 3.35, which means all of the independent variable (compensation = X1, X2 = work discipline) together there is a significant effect on work productivity variable (Y) on the mechanical PT Mulia Makmur Elektrikatama division.